Ultrasound- guided placement of double catheter in the right internal jugular vein: two case reports - Montes Tapia, Fernando Félix; Rodríguez Taméz, Antonio; Luévanos Gurrola, Karla; Garza Alatorre, Arturo Gerardo; O Cavazos, Manuel Enrique de la (Wolsters Kluver, 2014)
Central vascular access in critically ill paediatric patients is, many times, a challenge for physicians due to the number of lines needed for multiple infusions. We present ultrasound-guided placement of a double catheter in the right internal jugular vein in two patients that required multiple central lines for management.